RELATIONSHIP BETWEEN FAMILY SUPPORT AND VIA TEST EXAMINATION ON WOMEN OF CHILDBEARING AGE IN KLAYU VILLAGE, IN TEGALWARU AREA, JEMBER - Salsabila , Titanicova; Gumiarti, Gumiarti; Hidayati, Ainul (LPPM Universitas dr. Soebandi, 2025)
Introduction: Cervical cancer is the second most common cancer that attacks women. In Indonesia, this disease is still a serious health problem because the incidence of cervical cancer will continue to increase and can be the cause of death. In East Java, in 2019 as many as 3,341 women (1.2%) had positive via. The purpose of this study was to analyze the relationship between family support and iva test examination in women of childbearing age. The purpose of this study was to determine the relationship between family support and via test examination in women of childbearing age. Methods: The design in this study is quantitative analytics with a cross sectional approach. The population in this study was 110 married women of childbearing age, the sample of this study amounted to 86 using simple random sampling techniques. The measuring instruments used are questionnaires, and use the chi-square test. Results: Good family support 20.9%, sufficient family support 30.2%, less family support 48.8%. Respondents who had done via test 32.6%, while those who had never done via test 67.4%, the analysis test obtained p-value 0.000 < α 0.05. There is a significant relationship between family support and via testing. Discussion: The lack of family support causes women of childbearing age not to want to do an via test. Families should be able to support and encourage women of childbearing age in via test examinations, so that women of childbearing age can be motivated and not feel afraid.